2020
DOI: 10.3934/jimo.2019036
|View full text |Cite
|
Sign up to set email alerts
|

An application of crypto cloud computing in social networks by cooperative game theory

Abstract: In this paper, we mathematically associate Crypto Cloud Computing, that has become an emerging research area, with Cooperative Game Theory in the presence of uncertainty. In the sequel, we retrieve data from the database of Amazon Web Service. The joint view upon Crypto Cloud Computing, Cooperative Game Theory and Uncertainty management is a novel approach. For this purpose, we construct a cooperative interval game model and apply this model to Social Networks. Then, we suggest some interval solutions related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The limitations of this paper included the fact that other uncertainty approaches, such as parallelepiped uncertainty (Kara et al 2019 ), semialgebraic uncertainty (Kropat et al 2020 ), interval uncertainty (Ergun et al 2020 ), robust optimization (Goli et al 2019 ; Tirkolaee et al 2020 ), fuzzy uncertainty (Goli and Malmir 2020 ; Goli et al 2021 ), and metaheuristic approaches (Goli et al 2018 ; Pahlevan et al 2021 ) were not developed and compared to the current GMP approach. There are various directions and suggestions for further research.…”
Section: Conclusion and Further Researchmentioning
confidence: 98%
“…The limitations of this paper included the fact that other uncertainty approaches, such as parallelepiped uncertainty (Kara et al 2019 ), semialgebraic uncertainty (Kropat et al 2020 ), interval uncertainty (Ergun et al 2020 ), robust optimization (Goli et al 2019 ; Tirkolaee et al 2020 ), fuzzy uncertainty (Goli and Malmir 2020 ; Goli et al 2021 ), and metaheuristic approaches (Goli et al 2018 ; Pahlevan et al 2021 ) were not developed and compared to the current GMP approach. There are various directions and suggestions for further research.…”
Section: Conclusion and Further Researchmentioning
confidence: 98%
“…The work presented by [11] aims to identify various applications that crypto cloud computing has in the context of social networks. For this purpose, the researchers used cooperative game theory to deal with the uncertainty aspect of the cloud network.…”
Section: Application Of Game Theory In Cryptographymentioning
confidence: 99%
“…( 7)-( 10)), and apply right and left circular rotation on the initial secrete key SK as formulated in Eqs. (11), (12).…”
Section: Keystream Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that game theory increases the cryptography's efficiency and sophistication by solving some challenges inherent in typical cryptographic methods. Today, there is increasing interest among researchers in innovating security protocols and models that bridge the gap, integrating the practises practically applied in the game theory as well as in cryptography [10][11][12][13][14][15]. These techniques reveal promising outcomes when analysed based on security and performance.…”
Section: Introductionmentioning
confidence: 99%